THE IMPACT OF DIGITALIZATION, AUDITOR COMPETENCE, AND INDEPENDENCE ON EXTERNAL AUDIT QUALITY: A SYSTEMATIC LITERATURE REVIEW WITH A REMOTE AUDITING PERSPECTIVE - Robi'ah, Syamsiyatur; Yuhertiana, Indra; Sholihatin, Endang (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to examine the relationship between digitalization, auditor competence, and auditor independence in shaping audit quality within the context of remote auditing by employing a Systematic Literature Review (SLR) based on secondary data from published journal articles. A total of 20 peer-reviewed journal articles published between 2020 and 2025 were retrieved from Scopus, ScienceDirect, Emerald Insight, Google Scholar, and Sinta, selected through the PRISMA protocol, and analyzed using descriptive methods and thematic synthesis with the support of VOSviewer and Microsoft Excel. The findings indicate that digitalization of audits, encompassing big data analytics, artificial intelligence, cloud-based systems, and automated audit tools, serves as a major driver of improved audit efficiency and effectiveness. However, the successful implementation of digital audit technologies relies heavily on auditors' digital competence, including their ability to operate technological tools and conduct data-driven analysis. Furthermore, auditor independence remains a fundamental determinant of audit objectivity, particularly in the context of increased digital interaction and the growing reliance on remote auditing practices. Overall, the results confirm that the simultaneous interaction between technological adoption, professional competence, and auditor independence shapes audit quality in the digital era. This review presents key implications for auditors, audit firms, and regulators on how to enhance digital capabilities while maintaining professional integrity in technology-enabled audit environments.